The R563Q mutation of the β-subunit of the epithelial sodium channel gene associated with hypertensive disease and related complications in pregnancy - Viljoen, J. E. (Johanna E.) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Obstetrics and Gynaecology))--University of Stellenbosch, 2010.